Penyelenggaraan Sistem Pemerintahan Berbasis Elektronik di Kota Payakumbuh - Aulia, Tasya; Permana, Iip (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
The Electronic Based Government System (SPBE) is a digital governance framework implemented across various cities in Indonesia, including Payakumbuh in West Sumatra. Payakumbuh stands out with the highest SPBE index achievement among cities and regencies in West Sumatra in 2022. However, despite this notable achievement, the local government still faces challenges in effectively implementing SPBE. This study aims to identify both the facilitating factors and barriers to SPBE implementation in Payakumbuh. Employing a qualitative approach with descriptive methods, the research examines variables such as policy, stakeholder engagement, capability, process, and evaluation perspectives. Data collection involves interviews, observation, and documentation analysis. Analysis is conducted using the MAXQDA application. Findings reveal that while SPBE implementation in Payakumbuh is generally satisfactory, challenges persist, including budget constraints and insufficient IT-related human resource capacity. Continuous review processes are essential to address these barriers effectively.